Implementasi Program Bina Lingkungan Corporat Social Responsibility PT Pertamina Dalam Upaya Pelestarian Ekosistem Laut - siti qonaah qonaah (Universitas Bina Sarana Informatika, 2019)
Indonesia is a maritime country, The economic system of the people on the coast depends on the natural resources of the sea which produce various marine and fishery products. With a damaged marine environment due to illegal fishing, natural disasters, and damaged marine ecosystems activities that have the potential to protect the marine environment are needed. To preserve Indonesia's marine ecosystem, Pertamina is implementing an environmental development program which is one of its corporate social responsibility programs. Pertamina is committed to always prioritizing the balance and preservation of nature, the environment, society. Implementation of environmental development programs carried out includes providing support for Wasi, providing aid for environmental education props and Coral Reef Rehabilitation. This research is to find out the implementation of Pertamina's corporate social responsibility environmental development program in the preservation of marine ecosystems. In this study, researchers used a qualitative approach and case studies, as a research method that illustrates that the implementation of the corporate social environmental development program will benefit the community in the preservation of Indonesia's marine ecosystem. By improving human, natural and environmental welfare, Pertamina will be able to achieve sustainable business growth.Keywords: Corporate Social Responsibility, Preservation of Marine Ecosystems